PigSMART platform to improve profitability and reduce constraints in the Ugandan pig value chain - CGIAR Research Program on Livestock (2021)
The solution through the digital platforms have been piloted in the Uganda pig value chain in 2021. Feedback meetings have been held with stakeholders to share learnings